Revisiting the ethnomedicinal and ethnopharmacological applications of Baccharoides anthelmintica (L.) Moench: A literature and bibliometric analysis of 70 years - Tyagi, Atul; Negi, Shivani; Gargi, Baby; Bohra, Heena; Singhal, Parul; Mishra Rawat, Janhvi; Semwal, Prabhakar (Ethnobotany Research and Applications, 2025)
Background: Baccharoides anthelmintica (L.) Moench, commonly known as kaliziri, is a therapeutic plant of the Asteraceae family, used in Ayurveda for treating microbial, viral, and helminthic infections. The plant is broadly distributed, including in the Himalaya, and has gained scientific attention due to its bioactive potential. Therefore, in this review, we present the updated and quantified information on B. anthelmintica, along with a bibliometric analysis to measure the current research trends, hot topics, and key contributors. Methods: A mixed-methods approach was employed in this study, combining bibliometric analysis and systematic literature review. For bibliometric analysis, 234 articles were retrieved from Scopus, and 194 were selected after screening. VOSviewer and Bibliometrix software were used to analyze publication trends, key authors, and research focus areas. For the literature review, 6606 were collected (6510 from Google Scholar and 96 from PubMed). After screening, 209 relevant articles were selected to assess traditional uses, phytochemistry, pharmacological potential, and toxicity of B. anthelmintica. Results: The results indicate that: (1) publications on B. anthelmintica increased substantially since 2002, with an annual growth rate of 2.82 %; (2) India and China are the leading countries in terms of publication number and collaborations; (3) through the word cloud keyword analysis, the top three keywords identify the pharmacological significance of this plant; (4) Aisa H.A. and Turak A are the key authors and played significant roles in advancing the field. B. anthelmintica exhibits significant medicinal potential due to its bioactive compounds, which offer antioxidant, antimicrobial, and anticancer properties. Apart from this, there is a lack of clinical trials to confirm the safety and therapeutic efficacy of B. anthelmintica. It is also anticipated that upcoming research in this domain will emphasize molecular mechanisms and sustainable production of important bioconstituents. Conclusions: This review presents a bibliometric analysis that maps seven decades of global research on B. anthelmintica, highlighting key contributors, publication trends, and research gaps. Additionally, the literature review compiles updated information on the plant’s ethnomedicinal uses, phytochemistry, and pharmacology. Together, these findings offer a valuable foundation for future research and therapeutic exploration. Keywords: Baccharoides anthelmintica, Asteraceae, Bibliometric analysis, VOSviewer, Bioactive properties.